2017
DOI: 10.1038/s41598-017-15390-w
|View full text |Cite
|
Sign up to set email alerts
|

Decreased absolute numbers of CD3+ T cells and CD8+ T cells during aging in herpes zoster patients

Abstract: Herpes zoster (HZ) is an infectious dermatosis with high incidence worldwide. Age is a key risk factor for HZ, and postherpetic neuralgia (PHN) is the main sequelae. Until now, no index has been available to predict the pathogenesis of PHN, and rare reports have focused on the immune response during aging and PHN. In this study, we selected immunoglobulin and complement proteins as markers for humoral immunity, while T lymphocyte subsets and natural killer (NK) cells were selected as markers for cell immunity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
3
28
0
2
Order By: Relevance
“…The analysis of the number and percentage of CD3+ and CD3+CD56+ lymphocytes performed in our study corresponded to the investigations of the other groups and showed the increase in the number of NKT-like cells in the process of ageing [4,6,48] and decrease in the number and percentage of T lymphocytes [48][49][50].…”
Section: Nkt-like Cells Are "Non-classical" Nkt Cells Which Representsupporting
confidence: 84%
“…The analysis of the number and percentage of CD3+ and CD3+CD56+ lymphocytes performed in our study corresponded to the investigations of the other groups and showed the increase in the number of NKT-like cells in the process of ageing [4,6,48] and decrease in the number and percentage of T lymphocytes [48][49][50].…”
Section: Nkt-like Cells Are "Non-classical" Nkt Cells Which Representsupporting
confidence: 84%
“…Although we saw no changes in total T cell or CD8 + numbers, our mice are only aged to 14-16 months which is more like middle-aged humans (40-60 years) than truly elderly patients [41]. Human data suggests that the total number of T cells, and specifically CD8+ T cells, doesn't change between young (<40 years) and middle-aged (40-60 years) groups, however it significantly decreases in the old (>60 years) age group [42]. Perhaps if mice were aged >18-months we may see a T cell dependent effect.…”
Section: Discussionmentioning
confidence: 85%
“…C-reactive protein level was suggested to be inversely correlated to vaccine responsiveness in the elderly (95). Meanwhile, the absolute numbers of CD3 + , CD4 + , and CD8 + T cells in herpes zoster patients were significantly lower compared to those in the control (94). Given these findings, it will be important to further characterize age-associated changes in immune cell compartments in shingles patients on a larger scale.…”
Section: Vzvmentioning
confidence: 99%
“…The underlying mechanisms involved in VZV reactivation and susceptibility among the elderly or immunocompromised populations are currently unclear, although recent studies suggest aging cells as the cause of the inefficient clearance of virus-infected cells (91,92). Few markers that correlate with age-related severity in shingles or poor response to vaccination have also been identified (93)(94)(95). In particular, elderly residents in long-term care experience elevated incidence of shingles and post-herpetic neuralgia due to the high degree of immunosenescence, malnutrition, and existing chronic conditions.…”
Section: Vzvmentioning
confidence: 99%